Analysis of the Use of E-Lkpd on Student Learning Outcomes on Central Bank Material at State Senior High School 6 Palembang - Nurofiah; Hendri Gunawan; Nuryanti Permata Sari (Journal of Islamic Economics, 2025)
This study aims to examine the effect of using Electronic Student Worksheets (E-LKPD) on the learning outcomes of tenth-grade social science students. The research is motivated by the growing need for innovative digital learning media that can enhance student engagement and support effective understanding of learning materials in line with developments in educational technology. The study employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of two classes: Class X IPS 1 as the experimental group, which received instruction using E-LKPD, and Class X IPS 2 as the control group, which was taught using conventional direct instruction methods. Data were collected through learning outcome tests administered as pretests and posttests to both groups. The collected data were analyzed using a Paired Sample t-Test to identify improvements in learning outcomes within the experimental group and an Independent Samples t-Test to compare learning outcomes between the experimental and control groups. The results indicate that the average learning outcomes of students in the experimental class increased after the implementation of E-LKPD. However, the comparative analysis between the experimental and control groups revealed that the difference in learning outcomes was not statistically significant. These findings suggest that while E-LKPD has the potential to improve students’ learning outcomes within a group, its effectiveness is not significantly superior to conventional direct instruction. The study implies that the successful implementation of E-LKPD requires appropriate instructional strategies and strong teacher facilitation to achieve more significant learning outcomes.